2022
DOI: 10.1111/1440-1681.13736
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective potential of vanillic acid

Abstract: Nowadays, cardiovascular diseases (CVDs) are a global threat to public health, accounting for almost one‐third of all deaths worldwide. One of the key mechanistic pathways contributing to the development of CVDs, including cardiotoxicity (CTX) and myocardial ischaemia–reperfusion injury (MIRI) is oxidative stress (OS). Increased generation of reactive oxygen species (ROS) is closely associated with decreased antioxidant capacity and mitochondrial dysfunction. Currently, despite the availability of modern pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 142 publications
0
15
0
Order By: Relevance
“…Consistent with our study, several studies have demonstrated that VA can reduce mitochondrial dysfunction, oxidative stress and cardiotoxicity. These studies have shown that VA ameliorates cardiotoxicity with improvement mitochondrial function, reduction in ROS production, aggravation of antioxidative status, scavenging free radicals and inhibition of lipid peroxidation [ 21 , 42 – 47 ]. In addition to the beneficial effects of VA on cardiac mitochondria, this phenolic compound has promising effects on other mitochondria in different cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our study, several studies have demonstrated that VA can reduce mitochondrial dysfunction, oxidative stress and cardiotoxicity. These studies have shown that VA ameliorates cardiotoxicity with improvement mitochondrial function, reduction in ROS production, aggravation of antioxidative status, scavenging free radicals and inhibition of lipid peroxidation [ 21 , 42 – 47 ]. In addition to the beneficial effects of VA on cardiac mitochondria, this phenolic compound has promising effects on other mitochondria in different cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various studies have demonstrated that VA possesses diverse pharmacological activities such as anti-inflammatory, antioxidant, antihypertensive, antimicrobial and inhibition of snake venom activity [ 18 ]. Based on previous studies VA reduces ROS production and lipid peroxidation, improves mitochondrial function, scavenges free radicals, enhances antioxidative status, thereby decreasing cardiac dysfunction [ 21 , 22 ]. Therefore, in our current study, we have formulated a hypothesis that VA could potentially protect the harmful effects of methamphetamine on cardiac mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Phenolic acids 7 and 8 also possess antioxidant, cardioprotective and anti-inflammatory activities. 26,27 To the best of our knowledge, this is the first chemical report of C. bartramia plant.…”
Section: Characterisation Of Compounds 1−8mentioning
confidence: 90%
“…Furthermore, in vitro gut microbiota fermentation has shown that SA is strongly positively correlated with the increase of the Bifidobacterium genus [ 114 ]. Similarly, VA is famous for its ability to scavenge ROS, and it is correlated with different pharmacological activities such as antimicrobial, antifungal, antimutagen, hepatoprotective, and cardioprotective effects, to name a few [ 115 ]. Concerning this last aspect, it has been observed that treatment with VA results in an upregulation of eNOS expression and a downregulation of endothelin-1 [ 116 ].…”
Section: Anthocyanins and Their Gut-microbiota Derived Metabolites On...mentioning
confidence: 99%